Involvement of the Anterior Lobe of the Cerebellar Vermis in Perinatal Profound Hypoxia - Connolly, D.J.A.; Widjaja, E.; Griffiths, P.D. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: We report abnormal high T2 signal intensity in the anterior lobe of the cerebellar vermis that we believe was the result of profound hypoxic ischemic encephalopathy in the perinatal period in term infants. We tested the hypothesis that this sign was associated with other signs of significant perinatal hypoxic damage.METHODS: Thirty patients with clinically and radiologically confirmed perinatal profound hypoxia close to term were included in the study. The cranial MR images were reviewed by 2 pediatric neuroradiologists and were scored for the presence and severity of hypoxia/ischemia in the regions typically affected by profound hypoxia. The presence or absence of high T2 signal intensity in the vermis and other sites was correlated with the extent of damage in typically affected regions.RESULTS: Eighteen of 30 patients had high T2 signal intensity in the vermis. The presence of vermian damage correlated positively with radiologic evidence of severe hypoxic damage and extremely poor (0 or 1) 1-minute Apgar scores.CONCLUSIONS: High T2 signal intensity in the anterior lobe of the vermis probably represents gliosis secondary to hypoxia/ischemia and is related to the severity of damage in the term infant.